ANALISIS TENTANG RESPONS RADIKALISME SISWA BUDDHIS SEKOLAH MENENGAH PERTAMA DI KABUPATEN TEMANGGUNG - Metta, Giri; Sukodoyo, Sukodoyo; Kustiani, Kustiani (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2020)
Radical understanding at this time has been a crucial issue that is rapidly progressing. Research on the analysis of radicalism among Buddhist students in Temanggung Regency has a high background in the effectiveness of the world of education as a path of radical propagation. The purpose of this research is to know the conditions of radicalism among Buddhist students in Temanggung regency. The research methods used are quantitative desckriptive. The population in this research were Buddhist students in Temanggung regency which amounted to 250 people. Research samples amounted to 153 respondents from 6 schools determined by a simple random sampling. The collection instrument used is a poll. The validity of the poll is calculated by Bivariate Pearson and its reliability tests performed with Alpha Cronbach. The data analysis on this study uses descriptive statistics. The results showed a radicalism response from junior high school students in Temanggung Regency in high category with 71.56%. The radicalism response from the Buddhist students appears in cognitive, affective, and contemplative aspects. Cognitive aspects demonstrate a high understanding of radicalism by 54.8%. While the affective and contemplative aspects demonstrate a moderate attitude and behaviour to radical understanding, there is also a radicalism existence in the affective aspect of 6% and a conative aspect of 2%.